A Microbiological Analysis Of Smear Microscopy And Truenat Pcr Method In The Diagnosis Of Pulmonary Tuberculosis In A Tertiary Care Centre - Sanjeevani, Rohin; Tomar, Shama; Multani, Harman (Journal of Neonatal Surgery, 2025)
Fast and accurate diagnostic tests serve as vital role for detecting active tuberculosis, particularly in endemic countries like India. Since 2020, the World Health Organization is urging the usage of Truenat MTB Plus assay, a quick molecular test, as a first step in the detection of tuberculosis (TB). In order to guide future recommendations, the WHO emphasized the necessity of further assessing assay performance, including in individuals with HIV. The Truenat MTB/RIF molecular method is operated on rechargeable batteries, point-of-care, chip-based Real Time Polymerase Chain Reaction (RT-PCR) microdevice. In contrast to smear microscopy and solid culture, the Truenat MTB/RIF screening test's diagnostic accuracy in detecting pulmonary tuberculosis is to be assessed in this study. Over the period of a year prospective cross-sectional study is carried, where samples from suspected TB cases that met the inclusion criteria were subjected to Truenat RTPCR for MTB and Ziehl Neelsen (ZN) staining for smear microscopy. The study was conducted in Govt. Chest disease Hospital, Jammu, J&K. This study is carried on 248 patients with suspected pulmonary TB. The sensitivity, specificity and diagnostic accuracy for the diagnosis of tuberculosis were calculated for Acid Fast Bacilli (AFB) smear microscopy and the Truenat. Out of the total 248, 64 (16.66.%) patients were TB positive by TrueNat, and 51 (13.28%) as per smear microscopy. In low-resource environments, the Truenat MTB test is an affordable, quick molecular test that has good sensitivity and specificity for diagnosing pulmonary tuberculosis.